Representation of Racism in Antebellum Movie: Semiotic analysis of Roland Barthes - Sakina Shepia Maharani; Ainal Mardiyah; Nur Fatihah; Arita Destianingsih; Ari Satria (Journal of Pedagogy and Education Science, 2022)
Racism is a problem that has existed throughout the world since ancient times. Indonesia also does not escape the issue of racism. From the small issues that we did not realize until the big problems involving many parties. This racism makes the atmosphere uncomfortable and conducive if it has to involve many parties. Therefore, many filmmakers who try to raise the theme of racism become a film. Analysis of racism in “Antebellum” movie written and diricted by Gerard Bush and Christopher Renz. This research discuses the discrimination by white people to black people in Antebellum Movie. Black people and white people is separated by many rules that makes black people is intimidate, so racism is still growing up until generations. Racismmostly still happens in many countries, especially the country with a lot of majoritiesand minority groups with very strict differences in characteristics such as in the UnitedStates of America or other European countries.This research used semiotic analysis with the descriptive qualitative methods. This study aims to find out the contents of the film Antebellum, especially those related to forms of acts of racism. The lastresult of analysis, the researcher also found the Struggle that does by the black people in Antebellum Movie.